The epidemiology and prevention of suicide by hanging: a systematic review. - Gunnell, D; Bennewith, O; Hawton, K; Simkin, S; Kapur, N (2005)
BACKGROUND: Hanging is one of the most commonly used methods for suicide worldwide. In England and a number of other countries, its incidence has increased over the last 30 years. This review summarizes the published literature on suicide by hanging. The focus is on its epidemiology in England and on identifying potential means of prevention. METHODS: We searched Medline (1966-2003), Embase (1980-2003), CINAHL (1982-2003) and PsycINFO (1967-2003). As considerable research on suicides occurring in prisons and psychiatric hospitals in England and Wales has been carried out by the National Confidential Inquiry into Suicide and Homicide (Manchester) and the Prison Service's Safer Custody Group, we obtained additional information from these sources. RESULTS: Only a small proportion (around 10%) of hanging suicides occur in the controlled environments of hospitals, prisons, and police custody; the remainder occur in the community. The most commonly used ligatures (rope, belts, flex) and ligature points (beams, banisters, hooks, door knobs, and trees) are widely available; thus prevention strategies focused around restriction of access to means of hanging are of limited value. Around 50% of hanging suicides are not fully suspended--ligature points below head level are commonly used. Case fatality following attempted suicide by hanging is around 70%; the majority (80-90%) of those who reach hospital alive survive. CONCLUSION: Strategies to reduce suicide by hanging should focus on the prevention of suicide in controlled environments, the emergency management of 'near-hanging' and on the primary prevention of suicide in general. More research is required to better understand the recent rise in popularity of this method.